If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) = 4x + 10 Reorder the terms: 3(-1 + 2x) = 4x + 10 (-1 * 3 + 2x * 3) = 4x + 10 (-3 + 6x) = 4x + 10 Reorder the terms: -3 + 6x = 10 + 4x Solving -3 + 6x = 10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3 + 6x + -4x = 10 + 4x + -4x Combine like terms: 6x + -4x = 2x -3 + 2x = 10 + 4x + -4x Combine like terms: 4x + -4x = 0 -3 + 2x = 10 + 0 -3 + 2x = 10 Add '3' to each side of the equation. -3 + 3 + 2x = 10 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 10 + 3 2x = 10 + 3 Combine like terms: 10 + 3 = 13 2x = 13 Divide each side by '2'. x = 6.5 Simplifying x = 6.5
| 2c+1=7 | | 67/22-47/11 | | 2h+5d=9 | | 3x+7/3x=5x-8/4x | | 4h+4d=12 | | 15x^2+14x-13920=0 | | 15x-8=12x+7 | | 55x3-(-12)/8 | | 7y/3y=28 | | 14x^2+15x-13920=0 | | -(7xy-10)+2(5xy+4)= | | IV=10(7+11) | | IV= | | N*N-2=98 | | 174=48n-18 | | N*-2=98 | | 110-180= | | 0=3x^2+22x-24 | | 64=7x-13 | | 0.5x+3.8=-0.7 | | 23=6x-7 | | 1+9x=118 | | 3(3y+4)=-4y-27 | | 5x+10=8x-88 | | 3(3y+4)=-4-27 | | 8h-3=7h+2 | | -2.5(1-2n)-1.5n= | | 3[x+8]+6=39 | | 13=8x-3 | | 5/b^2x6/10 | | 16-5x=-49 | | 83.87=x*35 |